Impact of Love Language on Self-Esteem and Relationship Satisfaction of Partners in San Bartolome, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The impact of love language on self-esteem and relationship satisfaction of a long-termpartner was particularly interesting; people could view it scientifically as where the paircontinues to engage in a loving and healthy understanding of how to recognize their partner'sexpression of love after numerous years of relationship. Listening to one another and trying tounderstand how each other feels. Self-esteem and Satisfaction in Relationships are importantaspects of life and can determine relationship satisfaction. In close relationships, satisfactionis defined as the subjective attitude (satisfaction) and affective experience (happiness) inevaluating one's relationship.This study aimed to determine the Impact of Love language on the self-esteem andrelationship satisfaction of partners in San Bartolome Quezon City. A purposive samplingtechnique was used, which included 50 respondents from Barangay San Bartolome. Thisstudy utilized the Quantitative method, using a validated questionnaire of frequency andpercentage distribution.After gathering data and tabulating the results, it was found that there is no significant impactof love language on the self-esteem and relationship satisfaction of partners in SanBartolome.
Keywords: Psychology